Fostering entrepreneurship outcomes: an evaluation of fashion entrepreneurship program - Jamaluddin, Rahimah; Ali @ Hamid, Mass Hareeza; Abdul Kadir, Suhaida; Kamis, Arasinah; Mohamed, Suriani (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Entrepreneurship education has traditionally focused on formal education, but many initiatives have been taken currently parallel with the 21st century teaching and learning strategies by emphasizing learning by doing. The purpose of this paper was to examine the impact of entrepreneurship education on students’ entrepreneurship interest, intentions and competencies by implementing fashion entrepreneurship program. Purposive sampling techniques which involved screening process were conducted to select 40 students as the participants of the program. This study was held at Universiti Putra Malaysia for a period of five months. This program emphasized mentor-mentees system which involved 10 fashion entrepreneurs from the community. Participants were exposed to entrepreneurship seminars, business and skills trainings, e-marketing workshops, and entrepreneurship carnival as well as evaluation sessions. The findings show that participants’ perceptions’ towards their interest, intentions and competencies are high. Besides, it was found that a significant positive correlation exists between entrepreneurship interests with entrepreneurship intentions among the participants.